1996
DOI: 10.1113/jphysiol.1996.sp021330
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of the pattern of respiratory and cardiovascular response to systemic hypoxia in the piglet: the roles of adenosine.

Abstract: 1. In 3-day-old and 3-week-old spontaneously breathing piglets anaesthetized with Saffan, we have studied ventilatory and cardiovascular responses evoked by 5 min periods of hypoxia (breathing 10 and 6% 02). 2. In 3-day-old piglets both 10 and 6% 02 evoked an increase followed by a secondary fall in ventilation, a gradual tachycardia and a renal vasoconstriction, with an increase in femoral blood flow that was attributable to femoral vasodilatation. Arterial blood pressure rose initially but fell towards contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 39 publications
5
30
0
1
Order By: Relevance
“…This is of particular interest because there are reports in the literature indicating that the respiratory and cardiovascular responses evoked by systemic hypoxia in neonates are very similar to those we have seen in the rat: characteristically, ventilation increases and then falls and generally arterial pressure decreases (see 64,65). We have suggested this may arise because small mammals in general, whether the neonates of large mammalian species or the adults of small mammalian species, have a higher rate of O 2 consumption per gram body weight than larger mammals: they may therefore be more susceptible to the local metabolic effects of hypoxia when O 2 supply is reduced (55).…”
Section: The Gradual Effects Of Hypoxiasupporting
confidence: 54%
See 1 more Smart Citation
“…This is of particular interest because there are reports in the literature indicating that the respiratory and cardiovascular responses evoked by systemic hypoxia in neonates are very similar to those we have seen in the rat: characteristically, ventilation increases and then falls and generally arterial pressure decreases (see 64,65). We have suggested this may arise because small mammals in general, whether the neonates of large mammalian species or the adults of small mammalian species, have a higher rate of O 2 consumption per gram body weight than larger mammals: they may therefore be more susceptible to the local metabolic effects of hypoxia when O 2 supply is reduced (55).…”
Section: The Gradual Effects Of Hypoxiasupporting
confidence: 54%
“…Our experiments on newborn piglets indicate that this positive feedback loop is particularly likely to develop in individuals in whom the stimulatory effect of hypoxia on respiration is weak (64). Furthermore, our studies on rats that have been kept chronically hypoxic from birth in a hypoxic chamber, have shown that the bradycardia fall in arterial pressure and fall in cerebral blood flow induced by acute hypoxia is greatly exaggerated in these animals relative to those seen in controls (67).…”
Section: A Positive Feedback Loop?mentioning
confidence: 62%
“…This new finding narrows the window when a switch in adenosine's ability to depress breathing occurs. Previous studies in rats (5, 9), rabbits (4), and piglets (33), have reported a similar reduction of adenosinergic effect to occur within the first days or weeks after birth. Immediately after birth, as the partial pressure for oxygen increases, circulating levels of adenosine decrease (3,34), correlating with decreased extracellular levels in the brain (10), and thus the adenosinergic inhibition of breathing is reduced.…”
Section: Adenosinergic Respiratory Depression Decrease After Birthsupporting
confidence: 54%
“…The ventilatory response to hypoxia has been previously characterized in anesthetized piglets, and the current responses of diaphragm amplitude and frequency are consistent with prior studies (12)(13)(14)(15). A gradual increase in heart rate accompanied hypoxic exposure in these earlier studies (12,13).…”
Section: Discussionsupporting
confidence: 84%